A method to conduct longitudinal studies on indoor environmental quality and perceived occupant comfort. (March 2019) - Berquist, Justin; Ouf, Mohamed M.; O'Brien, William
Abstract: Buildings with transient occupancy such as malls and sport facilities pose a particular challenge for evaluating the effect of indoor environmental quality (IEQ) on occupant comfort due to 1) the difficulties in communicating with their occupants and 2) significant daily variations in their occupancy profiles. To this end, this research presents a method to conduct longitudinal studies in which IEQ and occupant comfort are continuously and simultaneously evaluated. The proposed method relies on using electronic occupant survey devices to enable data collection on a large scale and over longer durations. To validate the proposed method, it was implemented in a gymnastics center in eastern Ontario, Canada between September 2017 and February 2018. Over 1000 survey responses were collected and analyzed relative to prevailing IEQ conditions in the hour preceding each survey response. Analyses showed a stronger correlation between measured temperature and occupants' thermal comfort in comparison to the relationship between carbon dioxide concentrations and occupants' perception of the indoor air quality. The case study demonstrated the feasibility of the proposed research method which can be replicated on a wider scale in different building types, especially those with transient occupancy, to further investigate the effect of IEQ on occupant comfort. Highlights: A novel research method to conduct longitudinal studies of IEQ and comfort is presented. It relies on electronic survey devices to collect occupant responses on a large scale. The method was validated in a sport facility as a case study. Over 1000 survey responses were correlated to simultaneous IEQ measurements. Results show the method's feasibility especially for buildings with transient occupancy.